2021
DOI: 10.1186/s41155-020-00166-5
|View full text |Cite
|
Sign up to set email alerts
|

The moderation effect of identity exploration and basic psychological needs satisfaction on flourishing of Chinese rural children

Abstract: Most studies equate children’s mental health to a state of flourishing, which is a positive feeling and functions in their lives. Identity exploration and the satisfaction of three basic psychological needs are universal and crucial indicators of children’s flourishing. First, according to identity crisis theory, children in the pre-adolescence period begin to explore their own identities, a process which significantly affects their development and flourishing. Meanwhile, self-determination theory points out t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 56 publications
0
3
0
Order By: Relevance
“…In one of the rare studies that examined basic psychological needs as moderators between identity exploration and flourishing as an aspect of well-being (Guo et al, 2021), the results indicated that both identity exploration and basic psychological needs positively affected flourishing in children.…”
Section: Do Satisfaction or Frustration Of Basic Psychological Needs ...mentioning
confidence: 99%
“…In one of the rare studies that examined basic psychological needs as moderators between identity exploration and flourishing as an aspect of well-being (Guo et al, 2021), the results indicated that both identity exploration and basic psychological needs positively affected flourishing in children.…”
Section: Do Satisfaction or Frustration Of Basic Psychological Needs ...mentioning
confidence: 99%
“…Employee Flourishing refers to an individual's mental health by integrating emotional states and personal functioning from private and public perspectives (Guo et al, 2021). People who flourish have a high degree of mental health, as shown by a pattern of feeling well (emotional well-being) and functioning well (psychological and social well-being) (Keyes, & Annas, 2009).…”
Section: Literature Review and Hypothesis Development Employee Flouri...mentioning
confidence: 99%
“…Identity exploration is the degree to which individuals seek for personal values, beliefs, and goals and is considered as a crisis that is detrimental for the individual's development and well-being [15,20,21]. From this perspective, the adolescent who is in identity exploration lacks a clear understanding of self and specific goals about the future which could threaten the adolescent's identity development.…”
Section: Identity Development Of Adolescentsmentioning
confidence: 99%